Exploring the Intersection of Crime and Society in Deepti Kapoor’s Age of Vice - Sharma, Khum Prasad (Literary Studies, 2024)
This paper analyzes Deepti Kapoor’s Age of Vice, which depicts the discourse of darker side of modern Indian society, where crime, corruption, and inequality are prevalent. It follows three characters: Sunny, a rich criminal; Neda, a journalist; and Ajay, a loyal henchman. The narrative reflects on the complex social and cultural issues facing India today, such as corruption, casteism, gender inequality, and political unrest. It also challenges the stereotypes of crime fiction by mixing literary and genre elements. The narrative uses trauma as a methodology to explore the psychological and emotional effects of crime and violence on the characters and their relationships. It shows how trauma can be both a strength and a weakness, and how it can influence the way people see themselves and others. The narrative finds that crime and society are deeply connected in contemporary India and influence and contradict each other in complex ways. It further identifies how crime is not just a personal choice or morality, but also a result of systemic injustices and inequalities. The narrative presents a persuasive and insightful examination of the correlation between crime and society in modern India. It urges readers to reconsider their opinions on crime, justice, and ethics, and to grapple with the intricate realities of Indian society.